Hard x-ray source for flash radiography based on a 2.5 kJ plasma focus - Di Lorenzo, F. (2007)
A compact tabletop plasma focus suitable for hard x-ray imaging applications is presented. The hard x-ray emission was characterized by means of an effective energy analysis, based on images obtained with a single shot. The effective energy of the radiation was estimated to be around 83 keV from radiographic images of metallic pieces. Numerical calculations, based on validated codes, are presented to give a quantitative interpretation of the experimental results. Experimental demonstration of the suitability of this device for introspective imaging of metallic pieces is also given. © 2007 American Institute of Physics.